2021
DOI: 10.1097/mat.0000000000001488
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Numerically Predicted Shear Stress-dependent Dissipative Losses Within a Rotary Blood Pump

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(78 reference statements)
2
4
0
Order By: Relevance
“…The importance of establishing confidence in CFD setups was underlined by the initiative of the U.S. Food and Drug Administration (FDA) demonstrating that, despite good agreement of global flow properties between CFD-based computations and in-vitro measurements, local flow may be poorly resolved. [11][12][13] These findings are in line with recent studies indicating the debility of Reynolds-averaged Navier-Stokes (RANS) simulations to fully resolve viscous shear stresses, 11,12 and may imply that global validation is not sufficiently sensitive to draw conclusions about the validity of computed local quantities.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The importance of establishing confidence in CFD setups was underlined by the initiative of the U.S. Food and Drug Administration (FDA) demonstrating that, despite good agreement of global flow properties between CFD-based computations and in-vitro measurements, local flow may be poorly resolved. [11][12][13] These findings are in line with recent studies indicating the debility of Reynolds-averaged Navier-Stokes (RANS) simulations to fully resolve viscous shear stresses, 11,12 and may imply that global validation is not sufficiently sensitive to draw conclusions about the validity of computed local quantities.…”
supporting
confidence: 85%
“…Experimental validation was performed on a previously developed high-fidelity in-vitro testbench 12,14,16 ( Figure 2C ) that included the torque measuring shaft, the glass for optical access, and the electric drive for pump actuation (Supplementary Section 1, Supplemental Digital Content, http://links.lww.com/ASAIO/B63). A water-glycerol mixture (density: 1,110 ± 0.39 kg·m −3 ; dynamic viscosity: 3 ± 0.057 mPa·s) served as working fluid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study we found the impeller torque to be reliably resolved in a similar simulation setup. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…To additionally analyze the local distribution of hydraulic losses in both RBPs, local hydraulic power losses were computed in each individual compartment (Figure 2) based on a volumetric integration of both the viscous and turbulent dissipation as previously described. [ 20 ]…”
Section: Methodsmentioning
confidence: 99%